A comparative effectiveness analysis of treatment for latent tuberculosis infection using multilevel selection models. (May 2015) - Fluegge, Kyle R; Roe, Brian E
Aim : Nine months of isoniazid (9INH) is the gold standard for treatment of latent tuberculosis infection (LTBI). This paper compares the effectiveness of 9 months of isoniazid with 4 months of transitional rifampin (9H4R) to alternative therapies, including 9INH, 6 months of isoniazid (6INH) and 6 months of isoniazid with 4 months of transitional rifampin (6H4R), for treatment of LTBI.Materials & methods : Using an ethnically diverse clinic sample of 552 patients given treatment for LTBI with 9H4R, we use multilevel selection models to examine the adjusted comparative effectiveness of the regimens among ethnic groups that feature distinct genetic predispositions to side effects on INH. For unadjusted/absolute effectiveness, we simulated cost–effectiveness ratios for 4 months of rifampin (4RIF) and compared with bootstrapped confidence intervals for the alternative therapies.Results : There are variations in the comparative effectiveness across ethnic groups, with the most notable differences for 9H4R. For unadjusted/absolute effectiveness, 4RIF presents the greatest net benefit for US born black and African patients. For all other ethnic groups, 6H4R was the most effective.Conclusion : Patient ethnicity affects tolerance to INH. 9H4R was the most effective LTBI treatment for all ethnicities. However, this result heavily depends on whether adjustments are made for self-selection.